Návrh marketingového plánu - Petrová, Lenka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Hlavním předmětem diplomové práce je vypracování marketingového plánu pro nově vznikající společnost podnikající v účetnictví. První část se zabývá teorií marketingového plánování. Druhou část tvoří analýza současného stavu podniku a návrh marketingového plánu.

The goal of this diploma thesis is to devise marketing plan for newly emerging accoun-ting company. In the first part of this thesis is described theory of marketing planning. The second part deals with analysis of the current state of the business and marketing plan proposal.
Proposal of Marketing Plan
Keywords: Marketing; marketingový plán; marketingový mix; SWOT analýza; analýza trhu.; Marketing; marketing plan; marketing mix; SWOT analysis; market analysis.